Fraud examinations in white-collar crime investigations: convenience themes and review maturity - Gottschalk, Petter (Routledge, 2023)
"This book reviews a range of reports written by fraud examiners after completing internal investigations. These reports are normally kept secret and are the property of client organizations, which do not wish to disclose potential wrongdoing that can harm the reputation of the businesses. Fraud Examinations in White-Collar Crime Investigations was able to retrieve several recent reports, including foreign aid kickbacks, Russian favors to the Biathlon President, and Leon Black's deals with Jeffrey Epstein. While not claiming that the obtained reports are representative for the outcome of the private investigation industry, the reports do provide insights into the variety of issues that fraud examiners address in their internal investigations and the quality of their work. This book identifies convenience themes and assesses investigation maturity across the reports analyzed. It considers the motives of and opportunities for white-collar criminals, as well as their willingness to engage in unlawful activity, and assesses to what extent fraud examiners are either efficient or deficient in their work. A compelling read, this book will appeal to students and scholars of criminology, sociology, law politics and all those interested in fraud examinations in relation to white-collar crime"--